Effect of the dimensions of implant body and thread on bone resorption and stability in trapezoidal threaded dental implants: a sensitivity analysis and optimization. Issue 13 (2nd October 2020) - Niroomand, Mohammad Reza; Arabbeiki, Masoud
Abstract: Implant body and threads direct the functional loads from implant to bones. Appropriate design of implant helps implant stability. Therefore, implant length, diameter, and thread depth, width, pitch, and inner angle are assessed to recognize their effects on von-Mises stress and micromotion of implant and bones. The FE model of mandible with a threaded dental implant is modeled then the central composite design is used to assess the effects of parameters. The optimization is conducted to find the optimum design; however, it reduced the Max von-Mises stress in implant-abutment, cancellous, and cortical bones by 10%, 35%, and 27%, respectively.